2017
DOI: 10.1080/21663831.2017.1410863
|View full text |Cite
|
Sign up to set email alerts
|

Delayed damage accumulation by athermal suppression of defect production in concentrated solid solution alloys

Abstract: A combined experimental and computational evaluation of damage accumulation in ion-irradiated Ni, NiFe, and NiFeCoCr is presented. A suppressed damage accumulation, at early stages (low-fluence irradiations), is revealed in NiFeCoCr, with a linear dependence as a function of ion fluence, in sharp contrast to Ni and NiFe. This effect, observed at 16 K, is attributed to the complex energy landscape in these alloys that limits defect mobility and therefore enhances defect interaction and recombination. These resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…The delay of damage accumulation in the compositionally complex alloys has also been demonstrated to occur at low temperature. At 16 K, where long-range thermal migration of defects is frozen, the damage accumulation is delayed from Ni, NiFe, to NiCoFeCr, and the maximum disorder level is decreased in the same sequence (Velişa et al, 2017b). These data brought up an implication of the importance of Cr addition, stimulating another experiments targeting on verifying this issue ( Velişa et al, 2017a).…”
Section: Response To the Irradiation At Room And Low Temperaturesmentioning
confidence: 98%
See 1 more Smart Citation
“…The delay of damage accumulation in the compositionally complex alloys has also been demonstrated to occur at low temperature. At 16 K, where long-range thermal migration of defects is frozen, the damage accumulation is delayed from Ni, NiFe, to NiCoFeCr, and the maximum disorder level is decreased in the same sequence (Velişa et al, 2017b). These data brought up an implication of the importance of Cr addition, stimulating another experiments targeting on verifying this issue ( Velişa et al, 2017a).…”
Section: Response To the Irradiation At Room And Low Temperaturesmentioning
confidence: 98%
“…First, it has been considered to reduce of surviving defects in SP-CSAs under room and low temperature irradiations, by reducing the separation of interstitial and vacancy populations, enhancing the their interactions, and further promoting the defect recombination (Velişa et al, 2017b;Zhang Y. et al, 2017). Second, this mechanism has been considered to attribute to the qualitative different void distribution and the reduced swelling in SPCSAs (see Figures 7a,b): Interstitials migrate fast in Ni and NiCo, leaving the vacancies behind in the matrix oversaturated and aggregated into large voids.…”
Section: Linkage Between the Transport Properties And Irradiation Resmentioning
confidence: 99%
“…(from Cr to Cu) with similar atomic mass and size in a fcc structure, exhibit superior tensile strength and fracture toughness at both low and high temperatures [2][3][4][5][6][7], robust phase stability [8], ultrahigh lowtemperature toughness [ 9 ], superparamagnetism [ 10 ], superconductivity [ 11 ], and two orders of magnitude improvement in radiation tolerance [12]. New knowledge regarding concentrated alloys [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] has clearly revealed that compositional complexity (high chemical inhomogeneity), as opposed to the incorporation of dilute solutes [1], has a significant influence on defect dynamics that results in improved radiation performance [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Although radiation-induced defects and defect clusters are expected to be trapped or eliminated in these chemical or structural inhomogeneities, interactions of defects with GBs, however, can lead to GB chemical and structural changes that involve further complications and pose additional scientific questions. Substitutional solid solutions, with increasing structural and chemical complexities that are intrinsic in HEAs, cause unique site-to-site distortion and a locally disordered chemical environment, which may have a profound effect on the fundamental processes determining defect dynamics [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][18][19][20][21][22]. Such extreme elemental inhomogeneities in HEAs may strongly affect microstructure evolution in nanocrystalline films under ion irradiation.…”
Section: Introductionmentioning
confidence: 99%
“…62 This result, combined with the suppressed growth of vacancy clusters, is responsible for the delayed damage accumulation found in SP-CSAs. 63…”
Section: B MD Simulation: Displacement Cascade Evolution and Defect mentioning
confidence: 99%